Imagining Possible Worlds. Issue 2 (June 2018) - Oatley, Keith; Dunbar, Robin; Budelmann, Felix
The reading of fiction has been found to confer benefits, including increased empathy and understanding of others. Among ongoing research questions are those of how people engage in imagined worlds while keeping in touch with the currently perceived world, as well as how far stories were important in human evolution and how the brain is involved understanding them.